Association between Self-control and Aggression: An Analysis among Low Socioeconomic Status Individuals in East Coast of Malaysia - Mohammad Rahim Kamaluddin; Nadiah Syariani Md. Shariff; Norruzeyati Che Mohd Nasir; Ahmad Shukri Abdul Hamid; Geshina Ayu Mat Saat; Balan Rathakrishnan (2020)
Low socioeconomic status (Low SES) is often linked to aggressive and violent behaviour. However, there is a lack of studies in Malaysia that ascertain the relationship between Low SES, self-control and aggression. Therefore the aim of this present study was to identify the association between self-control and aggression levels among Low SES individuals. 140 adult Low SES males voluntarily participated in this quantitative study. A convenience sampling method was used to recruit the respondents in this study. The present study was an observational cross sectional study using self-administrated questionnaires carried out in the East Coast of Malaysia. Descriptive statistics and Pearson correlation test were employed for the purpose of analyses. The result evidenced statistically significant correlation between self-control and aggression levels (r = 0.444, 95% CI: 0.30, 0.57; p < 0.001). The findings of this study would provide some insights on the correlations of self-control and aggression among Low SES individuals from statistical and psychological perspectives.